Carolina Wren (Thryothorus ludovicianus) - Christopher M. Rusnak; Ronald F. Labisky (EDIS)
This document is Fact Sheet WEC 170, one of a series of the Department of Wildlife Ecology & Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published June 2003.